Fabrication of two dimensional polyethylene terephthalate nanofluidic chip using hot embossing and thermal bonding technique - Yin, Zhifu (Biomicrofluidics, 2014)
We present in this paper a method for obtaining a low cost and high replication precision 2D (two dimensional) nanofluidic chip with a PET (polyethylene terephthalate) sheet, which uses hot embossing and a thermal bonding technique. The hot embossing process parameters were optimized by both experiments and the finite element method to improve the replication precision of the 2D nanochannels. With the optimized process parameters, 174.67 ± 4.51 nm wide and 179.00 ± 4.00 nm deep nanochannels were successfully replicated into the PET sheet with high replication precision of 98.4%. O(2) plasma treatment was carried out before the bonding process to decrease the dimension loss and improve the bonding strength of the 2D nanofluidic chip. The bonding parameters were optimized by bonding rate of the nanofluidic chip. The experiment results show that the bonding strength of the 2D PET nanofluidic chip is 0.664 MPa, and the total dimension loss of 2D nanochannels is 4.34 ± 7.03 nm and 18.33 ± 9.52 nm, in width and depth, respectively. The fluorescence images demonstrate that there is no blocking or leakage over the entire micro- and nanochannels. With this fabrication technology, low cost polymer nanochannels can be fabricated, which allows for commercial manufacturing of nano-components.